2015
DOI: 10.1055/s-0035-1569279
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Oxycodone Exposure Alters CNS Endothelin Receptor Expression in Neonatal Rats

Abstract: Prenatal opioid exposure such as oxycodone is linked to significant adverse effects on the developing brain. Endothelin (ET) and its receptors are involved in normal development of the central nervous system. Opioid tolerance and withdrawal are mediated through ET receptors. It is possible that adverse effect of oxycodone on the developing brain is mediated through ET receptors. We evaluated brain ETA and ETB receptor expression during postnatal development in rats with prenatal oxycodone exposure. Timed pregn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 23 publications
1
20
1
Order By: Relevance
“…The majority of published research on NAS and/or antenatal opioid exposure focuses on neonatal and perinatal periods 6 , 9 18 . Whether these exposures have a long-term effect on childhood morbidity has not been elucidated; however, existing literature indicates that neonatal opioid exposure affects several neurobiologic processes in animal models 19 21 and results in neurocognitive and behavioral issues in humans 13 , 22 . Likewise, affected children may grow up in the setting of unstable living situations and other socioeconomic consequences of maternal substance use 13 , 23 which may be important mediators for adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of published research on NAS and/or antenatal opioid exposure focuses on neonatal and perinatal periods 6 , 9 18 . Whether these exposures have a long-term effect on childhood morbidity has not been elucidated; however, existing literature indicates that neonatal opioid exposure affects several neurobiologic processes in animal models 19 21 and results in neurocognitive and behavioral issues in humans 13 , 22 . Likewise, affected children may grow up in the setting of unstable living situations and other socioeconomic consequences of maternal substance use 13 , 23 which may be important mediators for adverse outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Few have exposed rodents to prenatal opioids other than morphine. [23][24][25][26][27][28][29] Here, we describe a novel model of perinatal fentanyl exposure by administering fentanyl in the drinking water of pregnant mouse dams until litters are weaned at postnatal day 21. This protocol resembles the entire human gestational period 30 and demonstrates its face validity to the human condition, in that it results in postnatal, adolescent and adult phenotypes reminiscent of those in exposed humans.…”
mentioning
confidence: 99%
“…However, a human study by Seaton et al has shown that oxy is concentrated in the breastmilk and offspring exposed via the breastmilk may receive less than 10% of a typical therapeutic oral infant dose (0.1-0.2 mg/kg) [32][33][34][35][36]. Despite this low dose, infant exposure to oxy via the breastmilk has been associated with central nervous system depression [37], and a number of animal studies have also revealed deficits in behavior and development associated with perinatal opioid exposure [12,[38][39][40]. Additionally, opiates can pass into the placenta and act on fetal opioid receptors [23][24][25].…”
Section: Discussionmentioning
confidence: 99%